UN Archives Geneva - Vereinte Nationen - Büro in Genf (2021)
"The UN Archives Geneva platform gives access to the fonds and collections managed by the United Nations Library and Archives in Geneva, including the archives of the United Nations in Geneva, the League of Nations (1919-1946), international peace movements (from 1870), and private paper." [self-description]